From Manna to Money:: The Narrative Structure of Yves Thériault's Aaron - Socken, Paul (Studies in Canadian Literature / Études en littérature canadienne, 1999)
Yves Theriault was a popular and prolific writer not known for his literary craftsmanship, yet his novel Aaron is a structural masterpiece. A close reading of the novel reveals how the structuring device of perfect symmetry identified by Renald Berube serves to illuminate its central themes: the confrontation between tradition and change in the modern world and the absence of a mediating force.